The Right to Stay or the Duty to Go? A Theoretical Framework for Distinguishing Ethical Facilitation from Coercive Displacement in Climate Adaptation Policy - Vareba, Dinebari David; Wadi, Elizabeth Oghenetega (Pinisi Journal of Social Science, 2025)
As climate change intensifies, governments worldwide are adopting “managed retreat” policies’ the strategic relocation of communities away from areas rendered uninhabitable by sea-level rise, flooding, and other climate impacts. While often framed as a pragmatic and protective adaptation strategy, these policies create profound ethical dilemmas that existing legal and policy frameworks are ill-equipped to address. The binary distinction between “voluntary” and “forced” migration obscures a complex grey zone of structural pressure where state action can render continued habitation impossible without issuing an explicit eviction order. This paper develops a theoretical framework for evaluating the ethical legitimacy of state-led climate relocation programs. Drawing on liberal political philosophy (Isaiah Berlin's concepts of negative and positive liberty; Philip Pettit's theory of non-domination), the Capabilities Approach (Amartya Sen and Martha Nussbaum), and social science literature on place attachment, the paper constructs a typology of pressures faced by climate-vulnerable communities. It distinguishes between: (1) Environmental Push (biophysical forces making life untenable), (2) Structural Constraint (the withdrawal of state services and infrastructure to incentivize departure), and (3) Direct Coercion (forced eviction under the guise of safety). The paper argues that the ethical legitimacy of managed retreat hinges on the preservation of what it terms the “Capability to Stay” ‘ the substantive freedom to remain in one's chosen place while maintaining access to basic rights and dignified living conditions. Using illustrative examples from coastal West Africa (Nigeria, Ghana), the United States Gulf Coast (Louisiana, Texas), and the Pacific Islands (Fiji, Vanuatu), the paper demonstrates how current policies often blur the line between protection and dispossession. It concludes by proposing an enhanced ethical framework for policymakers: “FPIC-Plus” (Free, Prior, and Informed Consent with a binding Capability Impact Assessment), adapted from Indigenous rights law, to govern climate relocation and ensure that the right to stay is not extinguished by the duty to go.